Epidemiology of cesarean in Peru - Távara, Luis (2015)
The authors present a collaborative study that prospectively has engaged 14 maternity hospitals in the public sector, 10 from the Ministry of Health (MOH) and 4 of the Peruvian Institute of Social Security (IPSS); Likewise 9 corresponded to Lima and 5 establishments were in other regions. Between March and July 1993 he managed to gather a total of 4205 cases of cesarean births attended between 21797 during the same period, representing a rate of 19.3%. There was no major difference in the rate between hospitals in Lima and provinces, but if a higher frequency was found in IPSS when compared with the MOH. The six most important causes of cesarean in Peru are: previous cesareada, acute fetal distress, breech birth, narrow pelvis, fetopelvic disproportion and toxemia, which remain more or less the same distribution between the MOH and IPSS. Some other epidemiological characteristics differ between patients treated in the IPSS and MOH and between those addressed in Lima and Provinces. One third of the cesarean postoperative complications, these being more frequent among women attending the MOH and in Lima. The perinatal mortality rate was 49 per thousand, a predominance of cases seen in the provinces. Maternal mortality was around 100 per hundred thousand and only occurred in the MOH. We comment on the caesarean section rate is rising and about the possibility and need to lower it, focusing on a better assessment of the causes that often lead to the operation.